A Unique Case of Incomplete Bifid Ureter and Associated Arterial Variations - Shivika Ahuja; Hannah Sullivan; Mark Noller; Yun Tan; Daniel Daly (Case Reports in Urology)
Introduction. Urogenital and vascular anomalies, including a left duplex kidney and a left aberrant renal artery that gave rise to the left ovarian artery, were observed in a 77-year-old female cadaver during a routine dissection. Description. A left aberrant renal artery, which gave rise to the left ovarian artery, was observed originating from the aorta 4 cm below the left renal artery. Two independent contributions to a bifid ureter were found originating from the hilum of the left kidney. These two contributions descended 12.4 cm and 10.6 cm, respectively, posterior to the left aberrant renal artery and lateral to the left ovarian artery before uniting anterior to the psoas major muscle to descend 12.7 cm to the bladder. Significance. While the duplex kidney is a relatively common congenital anomaly that can be asymptomatic, it can also potentially be associated with compression of renal vasculature or the ureter. Ureteral compression can then result in several pathologies including reflux, urinary tract infection (UTI), ureteropelvic junction obstruction, or hydronephrosis. Compression of renal and ovarian vasculature can result in altered blood flow to the kidney and ovary, potentially causing fibrosis, atrophy, or organ failure. Current imaging techniques alone are insufficient for correct diagnostics of such complications, and they must be supplemented with a thorough understanding of the respective anatomical variations.